Argumentative tools in the text of the textThe Rustumiya message as a model (مجلة إحالات, 2026)
The correlation between the new rhetoric style and the argumentative one considered to be thestrongest relationship which marked the hardest raciness to reach the goal of convincement and excitement in an explicit or implicit ways in various situations either literary or politically ones... etc directly or indirectly. One of these situations is the letter art or the Algerian sending in the Rosstoumy era, it is one of the prose texts which rely on the letter parts that is used to convince the recipient with a certain matter in a way of influencing him/her in a communicative language using such means of rhetoric arguments, people used tosearch for such language means which have both strategies the guidness, the charitable and hintable ones,and which includes argumentative means of the rhetoric style such as metaphor and enhancers and other phases of arguments which the letters get so as to answer the hypotheses of this paper, which has status and arole to impact ? what are the means which the sender depend on to get his point ?